The effect of variation of shear walls placement on the response of building structure using the Direct Displacement-Based Design method - Aji, Hanif Satria; Rosyidah, Anis; Saputra, Jonathan (SINERGI, 2022)
Shear walls’ placement in specific positions could develop different structural responses to the building and affect the structure’s strength to the received lateral loads. This research aims to find the variations in the shear walls’ placement on the structure’s response under the Direct Displacement Based Design (DDBD) method. The object of this research is the model of a 10-story reinforced concrete building located in Yogyakarta, Indonesia. Modelling of building structures is carried out in this study with four variations of shear wall placement. First, the walls are located at every building’s corner. The shear wall is then positioned in the core of the building, where the apertures have shrunk. Then, the shear wall is located on the edge of the building. Last, the shear wall is located on the edge of the building. ANOVA method is used to analyze the significant difference, i.e., variations in the walls’ placement. This research indicates the significant differences in the x-direction shear force and the y-direction moment The shear walls are suggested to be placed according to the building’s condition and the earthquake ground site’s class to produce an optimal structure to resist earthquake loads.